In vitro biocompatibility analysis of protein-resistant amphiphilic polysulfobetaines as coatings for surgical implants in contact with complex body fluids - Karthäuser, Jana F.; Gruhn, Dierk; Martínez Guajardo, Alejandro; Kopecz, Regina; Babel, Nina; Stervbo, Ulrik; Laschewsky, André; Viebahn, Richard; Salber, Jochen; Rosenhahn, Axel (Frontiers in Bioengineering and Biotechnology, 2024)
The fouling resistance of zwitterionic coatings is conventionally explained by the strong hydrophilicity of such polymers. Here, the in vitro biocompatibility of a set of systematically varied amphiphilic, zwitterionic copolymers is investigated. Photocrosslinkable, amphiphilic copolymers containing hydrophilic sulfobetaine methacrylate (SPe) and butyl methacrylate (BMA) were systematically synthesized in different ratios (50:50, 70:30, and 90:10) with a fixed content of photo-crosslinker by free radical copolymerization. The copolymers were spin-coated onto substrates and subsequently photocured by UV irradiation. Pure pBMA and pSPe as well as the prepared amphiphilic copolymers showed BMA content-dependent wettability in the dry state, but overall hydrophilic properties a fortiori in aqueous conditions. All polysulfobetaine-containing copolymers showed high resistance against non-specific adsorption (NSA) of proteins, platelet adhesion, thrombocyte activation, and bacterial accumulation. In some cases, the amphiphilic coatings even outperformed the purely hydrophilic pSPe coatings.